Oral hormone pregnancy tests and the risks of congenital malformations: A systematic review and meta-analysis - Heneghan, C; Aronson, J; Spencer, E; Holman, B; Mahtani, K; Perera, R; Onakpoya, I (F1000Research, 2018)
Background: Oral hormone pregnancy tests (HPTs), such as Primodos, containing ethinylestradiol and high doses of norethisterone, were given to over a million women from 1958 to 1978, when Primodos was withdrawn from the market because of concerns about possible teratogenicity. We aimed to study the association between maternal exposure to oral HPTs and congenital malformations. Methods: We have performed a systematic review and meta-analysis of case-control and cohort studies that included data from pregnant women and were exposed to oral HPTs within the estimated first three months of pregnancy, if compared with a relevant control group. We used random-effects meta-analysis and assessed the quality of each study using the Newcastle–Ottawa Scale for non-randomized studies. Results: We found 16 case control studies and 10 prospective cohort studies, together including 71 330 women, of whom 4209 were exposed to HPTs. Exposure to oral HPTs was associated with a 40% increased risk of all congenital malformations: pooled odds ratio (OR) = 1.40 (95% CI 1.18 to 1.66; P<0.0001; I2 = 0%). Exposure to HPTs was associated with an increased risk of congenital heart malformations: pooled OR = 1.89 (95% CI 1.32 to 2.72; P = 0.0006; I2=0%); nervous system malformations OR = 2.98 (95% CI 1.32 to 6.76; P = 0.0109 I2 = 78%); gastrointestinal malformations, OR = 4.50 (95% CI 0.63 to 32.20; P = 0.13; I2 = 54%); musculoskeletal malformations, OR = 2.24 (95% CI 1.23 to 4.08; P= 0.009; I2 = 0%); the VACTERL syndrome (Vertebral defects, Anal atresia, Cardiovascular anomalies, Tracheoesophageal fistula, Esophageal atresia, Renal anomalies, and Limb defects), OR = 7.47 (95% CI 2.92 to 19.07; P < 0.0001; I2 = 0%). Conclusions: This systematic review and meta-analysis shows that use of oral HPTs in pregnancy is associated with increased risks of congenital malformations.